Gender as a Moderator and its Moderating Effect on Relationship between Face Book Usage and the Academic Performance of Government University Undergraduates in Sri Lanka (Global Journal of Management and Business Research, 2019)
From this Article, it is considered that the moderating effect of gender, for Facebook usage, and the academic performance of government university undergraduates in Sri Lanka. From 984 government university undergraduates were the respondents of this study, and the respondents were from the University of Peradeniya, University of Kelaniya, University of Colombo, and University of Sri Jayewardenepura. Gender is a moderate variable for the study. And there are 534 male undergraduate respondents, and 450 female respondents responded to the questionnaire. Using a multi -group analysis method identified the moderating effect on both male and female groups. According to the analysis results, proved that gender moderates the relationship between social media usage (Facebook) and the academic performance of the government university undergraduates in Sri Lanka.
Keywords: university undergraduates; facebook usage; 1academic performance; gender